CDKN2BAS is associated with periodontitis in different European populations and is activated by bacterial infection. Issue 1 (26th October 2010) - Schaefer, Arne S; Richter, Gesa M; Dommisch, Henrik; Reinartz, Markus; Nothnagel, Michael; Noack, Barbara; Laine, Marja L; Folwaczny, Mathias; Groessner-Schreiber, Birte; Loos, Bruno G; Jepsen, Søren; Schreiber, Stefan
Abstract : Epidemiological studies have indicated a relationship between coronary heart disease (CHD) and periodontitis. Recently, CDKN2BAS was reported as a shared genetic risk factor of CHD and aggressive periodontitis (AgP), but the causative variant has remained unknown. To identify and validate risk variants in different European populations, we first explored 150 kb of the genetic region of CDKN2BAS including the adjacent genes CDKN2A and CDKN2B, covering 51 tagging single nucleotide polymorphisms (tagSNPs) in AgP and chronic periodontitis (CP) in individuals of Dutch origin (n=313). In a second step, we tested the significant SNP associations in an independent AgP and CP population of German origin (n=1264). For the tagSNPs rs1360590, rs3217992, and rs518394, we could validate the associations with AgP before and after adjustment for the covariates smoking, gender and diabetes, with SNP rs3217992 being the most significant (OR 1.48, 95% CI 1.19 to 1.85; p=0.0004). We further showed in vivo gene expression of CDKN2BAS, CDKN2A, CDKN2B, and CDK4 in healthy and inflamed gingival epithelium (GE) and connective tissue (CT), and detected a significantly higher expression of CDKN2BAS in healthy CT compared to GE (p=0.004). After 24 h of stimulation with Porphyromonas gingivalis in Streptococcus gordonii pre-treated gingival fibroblast (HGF) and cultured gingival epithelial cells (GECs), we observed a 25-fold and fourfold increase of CDKN2BAS gene expression in HGFs (p=0.003) and GECs (p=0.004), respectively. Considering the global importance of CDKN2BAS in the disease risk of CHD, this observation supports the theory of inflammatory components in the disease physiology of CHD.